Relaxation phenomena in cryogenic electrolytes: 9th International Conference on Cryocrystals and Quantum Crystals Odessa, Ukraine, September 2–8, 2012 (final part) - Shikin, V.; Chikina, I.; Nazin, S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Proposed is a scenario for development of observed relaxation phenomena in the cryogenic electrolyte with the structure of “liquid hydrogen + injected ions”. Ions of one sign are generated in the bulk of liquid hydrogen in the presence of external field E^ by a stationary radioactive source of ± ions at the bottom of the vessel. After accumulation near the free surface of the liquid with a finite density ns the ions can break its stability producing a pulse of ion current to the collector located above the liquid surface. The outlined process is periodically repeated. Its period contains information on the ion mobility and, which is most interesting, on dissociation (association) processes occurring in a system of charged particles placed in an external field. The cryogenic problem is a good model for dissociation in the presence of external field occurring in normal electrolytes without any external ion sources.